Variability in Fecundity–Body Size Relationships for Atlantic Salmon Associated With Body Condition and Life History - Tara L. Imlay; Cindy Breau; Julien April; J. Brian Dempson; John Hayward; Jason LeBlanc; Jenny E. Reid; David Roth; Jamie T. Vallis; Travis E. Van Leeuwen; Laura K. Weir (Fisheries Management and Ecology, 2026)
While body size is the primary driver of fecundity, other factors may contribute to variation in these relationships. Anadromous populations of Atlantic salmon ( Salmo salar ) have diverse life histories, and fisheries management relies on accurate fecundity estimates. We used Bayesian hierarchical models to determine the relationship between fecundity and fork length, and other life‐history characteristics, for 25 spawning populations throughout Eastern Canada. Fecundity was best modeled at the river level, increased with body size and condition, and decreased with mean egg diameter. Fecundity was higher for individuals that spent fewer years in freshwater as juveniles, and for consecutive repeat spawners compared with first‐time (or maiden) spawners that spent 1 year in the ocean. Lastly, there was interannual variability in the fecundity–body size relationship. These relationships should be used in conjunction with data on recent changes in body size and/or life‐history traits of populations to inform stock management.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Ocean acidification in Canada: the current state of knowledge and pathways for action - Kristina M. Barclay; Helen J. Gurney-Smith; Mohamed Ahmed; James R. Christian; Frédéric Cyr; Patrick J. Duke; Brent G. T. Else; Iria Gimenez; Martine Lizotte; M. Catherine Reader; Myron Roth; Krysten Rutherford; et al. (Frontiers in Marine Science, 2026)
Ocean acidification (OA) generally receives far less consideration than other climate stressors and related hazards, such as global warming and extreme weather events. Canada is uniquely vulnerable to OA given its extensive coastal oceans, the oceanographic processes in its three basins, accelerated warming and sea-ice melt, and extensive coastal communities and maritime economic sectors. Canada’s coastline is also home to extensive and diverse First Nations peoples with distinct histories, rights, title, laws, governance and whose traditions and cultures are extrinsically linked to the sea. However, there are currently very limited pathways to support OA action, mitigation, and/or adaptation in Canada, particularly at the policy level. Here, we present a first synthesis of the current state of OA knowledge across Canada's Pacific, Arctic, and Atlantic regions, including monitoring, modelling, biological responses, socioeconomic and policy perspectives, and examples of existing OA actions and efforts at local and provincial levels. We also suggest a step-wise pathway for actions to enhance the coordinated filling of OA knowledge gaps and integration of OA knowledge into decision-making frameworks. The goals of these recommendations are to improve our ability to respond to OA in Canada, and minimize risks to coastal marine environments and ecosystems, vulnerable sectors, and communities.

Air pollution exposure assessment for preschool children: Addressing spatial and temporal variations and social inequities - Å.K. Watne; M. Azzouz; P. Molnar; L. Stockfelt; J. Lindén; E. Johansson; M. Laurelin; T. Wisell; H. Lundström; A. Roth; S. Jutterström; J. Moldanova; et al. (Journal of Environmental Management, 2025)

Cue relevance during navigation is a function of scale and experience - Aaron R. Krochmal; Timothy C. Roth; Nathaniel T. Simmons (Animal Behaviour, 2025)

Long-term field study on corn response to sulfur fertilization in Iowa, USA - Cecilia Crespo; John L. Kovar; Chad E. Hart; Richard T. Roth; Peter L. O’Brien; Sabrina J. Ruis (Field Crops Research, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Factors influencing detection of invasive Red Swamp Crayfish Procambarus clarkii (Girard, 1852) in Michigan ponds - William R. Budnick; Dan Hayes; Seth Herbst; Jeannette Kanefsky; Lucas Nathan; Brian M. Roth; Nicholas M. Sard; Kim T. Scribner; Kelley Smith; Sara Thomas (Hydrobiologia, 2024)

Cover crop impacts on nitrogen losses and environmental damage cost - Frank E. Johnson; Richard T. Roth; Michael D. Ruffatti; Shalamar D. Armstrong (Agriculture, Ecosystems & Environment, 2024)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Environment-induced heat stress causes structural and biochemical changes in the heart - Melissa Roths; Alyssa D. Freestone; Tori E. Rudolph; Alyona Michael; Lance H. Baumgard; Joshua T. Selsby (Journal of Thermal Biology, 2023)

Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Quantifying the fate of nitrogen from cereal rye root and shoot biomass using 15N - Richard T. Roth; Corey G. Lacey; James J. Camberato; Shalamar D. Armstrong (Nutrient Cycling in Agroecosystems, 2023)

Multiple sources implicated in the red swamp crayfish invasion in Michigan, USA - N. M. Sard; K. R. Smith; B. M. Roth; L. R. Nathan; S. J. Herbst; K. T. Scribner (Biological Invasions, 2023)

Chemical Stability and Bioactivity of tanshinone I, tanshinone IIA, cryptotanshinone and dihydrotanshinone in in vitro test systems - Annika Roth; Piwen Zhao; Sebastian T. Soukup; Claudia Guigas; Joachim Stärke; Sabine E. Kulling; Patrick Diel (Toxicology Letters, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

A functional Wood–Ljungdahl pathway devoid of a formate dehydrogenase in the gut acetogens Blautia wexlerae , Blautia luti and beyond - Raphael Trischler; Jennifer Roth; Matthew T. Sorbara; Xenia Schlegel; Volker Müller (Environmental Microbiology, 2022)
Summary Species of the genus Blautia are typical inhabitants of the human gut and considered as beneficial gut microbes. However, their role in the gut microbiome and their metabolic features are poorly understood. Blautia schinkii was described as an acetogenic bacterium, characterized by a functional Wood–Ljungdahl pathway (WLP) of acetogenesis from H 2 + CO 2 . Here we report that two relatives, Blautia luti and Blautia wexlerae do not grow on H 2 + CO 2 . Inspection of the genome sequence revealed all genes of the WLP except genes encoding a formate dehydrogenase and an electron‐bifurcating hydrogenase. Enzyme assays confirmed this prediction. Accordingly, resting cells neither converted H 2 + CO 2 nor H 2 + HCOOH + CO 2 to acetate. Carbon monoxide is an intermediate of the WLP and substrate for many acetogens. Blautia luti and B . wexlerae had an active CO dehydrogenase and resting cells performed acetogenesis from HCOOH + CO 2 + CO, demonstrating a functional WLP. Bioinformatic analyses revealed that many Blautia strains as well as other gut acetogens lack formate dehydrogenases and hydrogenases. Thus, the use of formate instead of H 2 + CO 2 as an interspecies hydrogen and electron carrier seems to be more common in the gut microbiome.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Implementation of a Medication for Addiction Treatment (MAT) and Linkage Program by Leveraging Community Partnerships and Medical Toxicology Expertise - Gillian A. Beauchamp; Lexis T. Laubach; Samantha B. Esposito; Ali Yazdanyar; Paige Roth; Priyanka Lauber; Jamie Allen; Nathan Boateng; Samantha Shaak; David B. Burmeister (Journal of Medical Toxicology, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Application and clinical impact of the RESIST-4 O.K.N.V. rapid diagnostic test for carbapenemase detection in blood cultures and clinical samples - Sophie Roth; Fabian K. Berger; Andreas Link; Anna Nimmesgern; Philipp M. Lepper; Niels Murawski; Jörg T. Bittenbring; Sören L. Becker (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
Invasive infections caused by carbapenemase-producing bacteria are associated with excess mortality. We applied a rapid diagnostic test (RDT) on clinical samples with an elevated likelihood of carbapenemase-producing bacteria and documented its impact on antibiotic treatment decisions. Among 38 patients, twelve tested positive for infections caused by carbapenemase-producing bacteria (31.6%), mainly in blood cultures. KPC ( n = 10) was more frequent than OXA-48 ( n = 2). RDT-based carbapenemase detection led to a treatment modification to ceftazidime/avibactam-containing regimens in all patients before detailed antibiotic testing results became available. Eleven patients (92%) survived the acute infection, whereas one patient with a ceftazidime/avibactam- and colistin-resistant OXA-48-positive isolate died.

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Constraints to the capacity of smallholder farming households to adapt to climate change in South and Southeast Asia - Peter R. Brown; Sharmin Afroz; Lytoua Chialue; T. Chiranjeevi; Sotheary El; Clemens M. Grünbühel; Iqbal Khan; Cathy Pitkin; V. Ratna Reddy; Christian H. Roth; Silinthone Sacklokham; Liana J. Williams (Climate and Development, 2019)

Sex Differences in Early Postnatal Microglial Colonization of the Developing Rat Hippocampus Following a Single-Day Alcohol Exposure - M. J. Ruggiero; K. E. Boschen; T. L. Roth; A. Y. Klintsova (Journal of Neuroimmune Pharmacology, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

Regulation of Cell Surface CB2 Receptor during Human B Cell Activation and Differentiation - Julie T. Castaneda; Airi Harui; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2017)

A novel forest state assessment methodology to support conservation and forest management planning - T. Standovár; F. Szmorad; B. Kovács; K. Kelemen; M. Plattner; T. Roth; Zs. Pataki (Community Ecology, 2016)

Increased blubber cortisol in ice-entrapped beluga whales (Delphinapterus leucas) - Marci R. Trana; James D. Roth; Gregg T. Tomy; W. Gary Anderson; Steven H. Ferguson (Polar Biology, 2016)

Exposure to Δ9-Tetrahydrocannabinol Impairs the Differentiation of Human Monocyte-derived Dendritic Cells and their Capacity for T cell Activation - Michael D. Roth; Julie T. Castaneda; Sylvia M. Kiertscher (Journal of Neuroimmune Pharmacology, 2015)

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

Impact of raw pig slurry and pig farming practices on physicochemical parameters and on atmospheric N2O and CH4 emissions of tropical soils, Uvéa Island (South Pacific) - E. Roth; P. Gunkel-Grillon; L. Joly; X. Thomas; T. Decarpenterie; I. Mappe-Fogaing; C. Laporte-Magoni; N. Dumelié; G. Durry (Environmental Science and Pollution Research, 2014)

Selection of Multiple Umbrella Species for Functional and Taxonomic Diversity to Represent Urban Biodiversity - T. SATTLER; G. B. PEZZATTI; M. P. NOBIS; M. K. OBRIST; T. ROTH; M. MORETTI (Conservation Biology, 2014)
Surrogates, such as umbrella species, are commonly used to reduce the complexity of quantifying biodiversity for conservation purposes. The presence of umbrella species is often indicative of high taxonomic diversity; however, functional diversity is now recognized as an important metric for biodiversity and thus should be considered when choosing umbrella species. We identified umbrella species associated with high taxonomic and functional biodiversity in urban areas in Switzerland. We analyzed 39,752 individuals of 574 animal species from 96 study plots and 1397 presences of 262 plant species from 58 plots. Thirty‐one biodiversity measures of 7 taxonomic groups (plants, spiders, bees, ground beetles, lady bugs, weevils and birds) were included in within‐ and across‐taxa analyses. Sixteen measures were taxonomical (species richness and species diversity), whereas 15 were functional (species traits including mobility, resource use, and reproduction). We used indicator value analysis to identify umbrella species associated with single or multiple biodiversity measures. Many umbrella species were indicators of high biodiversity within their own taxonomic group (from 33.3% in weevils to 93.8% in birds), to a lesser extent they were indicators across taxa. Principal component analysis revealed that umbrella species for multiple measures of biodiversity represented different aspects of biodiversity, especially with respect to measures of taxonomic and functional diversity. Thus, even umbrella species for multiple measures of biodiversity were complementary in the biodiversity aspects they represented. Thus, the choice of umbrella species based solely on taxonomic diversity is questionable and may not represent biodiversity comprehensively. Our results suggest that, depending on conservation priorities, managers should choose multiple and complementary umbrella species to assess the state of biodiversity. Selección de Múltiples Especies Paraguas para la Diversidad Funcional y Taxonómica para Representar la Biodiversidad Urbana

Assessment of Juvenile Pigs to Serve as Human Pediatric Surrogates for Preclinical Formulation Pharmacokinetic Testing - Wyatt J. Roth; Candice B. Kissinger; Robyn R. McCain; Bruce R. Cooper; Jeremy N. Marchant-Forde; Rachel C. Vreeman; Sophia Hannou; Gregory T. Knipp (The AAPS Journal, 2013)

Microhabitat heterogeneity in temperate forests: is distance to stems affecting ground-dwelling spider communities? - T. Ziesche; M. Roth (Community Ecology, 2013)

Differential Expression of Intracellular and Extracellular CB2 Cannabinoid Receptor Protein by Human Peripheral Blood Leukocytes - Julie T. Castaneda; Airi Harui; Sylvia M. Kiertscher; Jeffrey D. Roth; Michael D. Roth (Journal of Neuroimmune Pharmacology, 2013)

Differential hippocampal gene expression is associated with climate‐related natural variation in memory and the hippocampus in food‐caching chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; R. Kramer; F. Schilkey; A. M. van der Linden (Molecular Ecology, 2013)
There is significant and often heritable variation in cognition and its underlying neural mechanisms, yet specific genetic contributions to such variation are not well characterized. Black‐capped chickadees present a good model to investigate the genetic basis of cognition because they exhibit tremendous climate‐related variation in memory, hippocampal morphology and neurogenesis rates throughout the North American continent, and these cognitive traits appear to have a heritable basis. We examined the hippocampal transcriptome profiles of laboratory‐reared chickadees from the two most divergent populations to test whether differential gene expression in the hippocampus is associated with population differences in spatial memory, hippocampal morphology and adult hippocampal neurogenesis rates. Using high‐resolution mRNA sequencing coupled to a de novo transcriptome assembly, we generated 23 295 consensus sequences, which predicted 16 206 protein sequences with 13 982 showing high similarity to known protein sequences or conserved hypothetical proteins in other species. Of these, we identified differential expression in nearly 380 genes, with 47 genes specifically linked to neurogenesis, apoptosis, synaptic function, and learning and memory processes. Many of the other differentially expressed genes, however, may be associated with other functions. Our study presents the first avian hippocampal transcriptome, and it is the first study identifying differential gene expression associated with natural variation in cognition and the hippocampus. Our results provide additional support to the hypothesis that population differences in memory, hippocampal morphology and neurogenesis in chickadees have likely resulted from natural selection that appears to act on memory and its underlying neural mechanisms.

Population genetic structure and its implications for adaptive variation in memory and the hippocampus on a continental scale in food‐caching black‐capped chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; T. M. Burg; M. J. Braun; B. S. Davidson (Molecular Ecology, 2012)
Food‐caching birds rely on stored food to survive the winter, and spatial memory has been shown to be critical in successful cache recovery. Both spatial memory and the hippocampus, an area of the brain involved in spatial memory, exhibit significant geographic variation linked to climate‐based environmental harshness and the potential reliance on food caches for survival. Such geographic variation has been suggested to have a heritable basis associated with differential selection. Here, we ask whether population genetic differentiation and potential isolation among multiple populations of food‐caching black‐capped chickadees is associated with differences in memory and hippocampal morphology by exploring population genetic structure within and among groups of populations that are divergent to different degrees in hippocampal morphology. Using mitochondrial DNA and 583 AFLP loci, we found that population divergence in hippocampal morphology is not significantly associated with neutral genetic divergence or geographic distance, but instead is significantly associated with differences in winter climate. These results are consistent with variation in a history of natural selection on memory and hippocampal morphology that creates and maintains differences in these traits regardless of population genetic structure and likely associated gene flow.

Using the spectral scaling exponent for validation of quantitative precipitation forecasts - T.-Y. Koh; B. C. Bhatt; K. K. W. Cheung; C. K. Teo; Y. H. Lee; Matthias Roth; Purnawirman (Meteorology and Atmospheric Physics, 2012)

ICUC‐7 Urban Climate Special Issue - M. Roth; R. Emmanuel; T. Ichinose; J. Salmond (International Journal of Climatology, 2011)

A simulation of food‐web interactions leading to rainbow smelt Osmerus mordax dominance in Sparkling Lake, Wisconsin - B. M. Roth; T. R. Hrabik; C. T. Solomon; N. Mercado‐Silva; J. F. Kitchell (Journal of Fish Biology, 2010)
A process‐based simulation model was used to examine the nature and intensity of food‐web interactions that allow Osmerus mordax to dominate invaded lakes. The model simulates food‐web interactions among linked populations of O. mordax , Coregonus artedi and Sander vitreus . Simulations indicated that O. mordax dominate where: (1) adult O. mordax prey on young‐of‐the‐year (YOY) C. artedi , (2) YOY O. mordax negatively affect YOY S. vitreus through competition and (3) adult S. vitreus experience moderate fishing mortality. Osmerus mordax dominated simulations across a broad range of variable values that regulated competition and predation, and displayed threshold responses to increasing angler harvest. Consequently, angler harvest should be carefully managed in lakes susceptible to O. mordax invasions because the alternative could lead to fishery collapse.

Is the age of forest habitats affecting the reproductive rate of generalist predatory ground beetle species? - T. Ziesche; M. Roth (Community Ecology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Temporal dynamics of the urban heat island of Singapore - Winston T. L. Chow; Matthias Roth (International Journal of Climatology, 2006)

Effect of In Vivo Administration of Ethylmalonic Acid on Energy Metabolism in Rat Tissues - Gustavo da C. Ferreira; Karina Roth André; Patrícia Fernanda Schuck; Carolina M. Viegas; Anelise Tonin; Daniella de Moura Coelho; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Moacir Wajner (Metabolic Brain Disease, 2006)

Seasonal cycle in vitamin A1/A2-based visual pigment composition during the life history of coho salmon (Oncorhynchus kisutch) - S. E. Temple; E. M. Plate; S. Ramsden; T. J. Haimberger; W.-M. Roth; C. W. Hawryshyn (Journal of Comparative Physiology A, 2006)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

Water flow and solute transport in furrow-irrigated fields - Fariborz Abbasi; Jan Feyen; Robert L. Roth; Mike Sheedy; M. T. van Genuchten (Irrigation Science, 2003)

Using Environmental Stressor Information to Predict the Ecological Status of Maryland Non-tidal Streams as Measured by Biological Indicators - J. H. Vølstad; N. E. Roth; G. Mercurio; M. T. Southerland; D. E. Strebel (Environmental Monitoring and Assessment, 2003)

Interactions of temperature and angiotensin II in paraventricular neurons of rats in vitro - Mathias Dewald; Hans A. Braun; Martin T. Huber; Detlev Zwingmann; Joachim Roth; Karlheinz Voigt (Pflügers Archiv - European Journal of Physiology, 2002)

The Occurrence and Distribution of Selected Trace Elements in the Upper Rio Grande and Tributaries in Colorado and Northern New Mexico - H. E. Taylor; R. C. Antweiler; D. A. Roth; T. I. Brinton; D. B. Peart; D. F. Healy (Archives of Environmental Contamination and Toxicology, 2001)

Two-dimensional gel analysis of apoptosis-specific p53 isoforms induced by 2-methoxyestradiol in human lung cancer cells - T. Mukhopadhyay; J. A. Roth; S. A. Acosta; S. A. Maxwell (Apoptosis, 1998)

Aerodynamic Roughness of Urban Areas Derived from Wind Observations - C.S.B. Grimmond; T. S. King; M. Roth; T. R. Oke (Boundary-Layer Meteorology, 1998)

Colonoscope flexural rigidity measurement - J. A. Wehrmeyer; J. A. Barthel; J. P. Roth; T. Saifuddin (Medical & Biological Engineering & Computing, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

Hypnotic self administration: forced-choice versus single-choice - T. Roehrs; Bonita Pedrosi; Leon Rosenthal; Frank Zorick; Thomas Roth (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)